الدافعية العقلية وعلاقتها بأساليب التعلم لدى طلبة علم النفس بجامعة بوضياف-المسيلة- -دراسة ميدانية على عينة من طلبة السنة الثانية ماستر إرشادوتوجيه - دهيمي جمال; بن صالح خالد; اشراف: نوال صديقي (جامعة محمد بوضياف -المسيلة, 2025)
هدفت الدراسة الحالية الى التعرف على: طبيعة العلاقة بين الدافعية العقلية وأساليب التعلم لعينة من طلبة سنة ثانية ماستر تخصص ارشاد والتوجيه ، وذلك من خلال دراسة ميدانية من جامعة محمد بوضياف بالمسيلة، أجريت الدراسة على عينة تتكون من(183) طالبا وطالبة، كما اعتمد الطالبين على المنهج الوصفي الارتباطي، مستخدما في ذلك مقياس الدافعية العقليةمن أعده كل من أنتوستل وتايت (Entwistle&Tait, 1994)، والذي قام بتعديله دوف (Duff.1997)، ومقياس أساليب التعلم من اعداد إختبار كاليفورنيا للدافعية العقلية وقد تم بناء هذه الأداة من قبل جيانكارول وفاشيون (Giancarol&facion.1998)،وبعد اجراء الدراسة الميدانية وجمع البيانات والمعلومات وتبويبها ومعالجتها احصائياً، تم التوصل الى أهم النتائج الآتي ذكرها: ⇐ توجد علاقة إرتباطية دالة إحصائيا بين الدافعية العقلية وأساليب التعلم لدىطلبة السنة الثانية ماستر تخصص ارشاد والتوجيه، في جامعة محمد بوضياف المسيلة ⇐ مستوى الدافعية العقلية مرتفع لدى عينة طلبة السنة الثانية ماستر تخصص ارشاد والتوجيه، في جامعة محمد بوضياف المسيلة ⇐ عدم وجود فروق دالة احصائيا تبعا لمتغير الجنس لدى عينة من طلبة السنة الثانية ماستر تخصص ارشاد وتوجيه جامعة المسيلة. الكلمات المفتاحية: الدافعية العقلية، أساليب التعلم، طلبة ماستر02 ارشاد وتوجيه Abstract: The current study aimed to identify: the nature of the relationship between mental motivation and learning styles for a sample of second-year master’s students specializing in counseling and guidance, through a field study from Mohamed Boudiaf University in M’sila. The study was conducted on a sample consisting of (183) male and female students. The two students also relied on The descriptive, correlational approach, using the Mental Motivation Scale prepared by Entwistle & Tait (1994), which was modified by Duff (1997), and the Learning Styles Scale prepared by the California Mental Motivation Test. This tool was built by Giancarol & Facion (1998), after conducting a field study and collecting... Data and information were classified and processed statistically. The following most important results were reached: There is a statistically significant correlation between mental motivation and learning styles among second-year master’s students specializing in guidance and guidance, at the University of Mohammed Boudiaf M’sila.⇐ The level of mental motivation is high among a sample of second-year master’s students specializing in counseling and guidance, at the University of Mohamed Boudiaf, M’sila.⇐ There are no statistically significant differences according to the gender variable among a sample of second-year master’s students majoring in counseling and guidance at the University of M’sila. Keywords: mental motivation, learning styles (Antostell and Tait).